IDENTIFYING AND ELIMINATING THE SCALE OF THE HIDDEN ECONOMY IN THE SERVICE SECTOR (British Journal of Global Ecology and Sustainable Development, 2024)
The article notes that despite the implementation of several strict measures by the government of our country over the past five years to combat the hidden economy, its scale remains high to this day. It also highlights that although the share of the service sector in the structure of the country’s GDP has been growing year by year, the scale of the hidden economy in this sector is also significant. Based on this, the authors have analyzed instances of the hidden economy identified in the service sector among economic entities in the Samarkand region and have presented their proposals and opinions on its prevention and elimination.